ANALISIS PENGARUH JOB INSECURITY DAN KEPUASAN KOMPENSASI TERHADAP TURNOVER INTENTION SERTA DAMPAKNYA PADA KINERJA KARYAWAN (Studi Pada PDAM Kabupaten Semarang) - Ajiputra, Mirza Setyawan; Yuniawan, Ahyar (Diponegoro Journal of Management, 2016)
Human resources play an important role in a company since human is the determiner of the company. Company’s success is measured by the performance of employees. High employee performance makes the success of the company is also getting higher. The purpose of this study is to analyze the influence of job insecurity and compensation satisfaction on turnover intention and the effect on  employee performance.            The population in this study were employees of PDAM Kabupaten Semarang. This study was conducted by distributing questionnaires to a sample of 79 employee using purposive sampling techniques. Data analysis method used is multiple linear regression analysis. Mechanical testing data used this study include the path analysis and sobel test to test the effect of mediation.The result showed that job insecurity positive and significant influence to turnover intention, compensation satisfaction negative and significant influence to turnover intention, turnover intention negative and significant influence to employee performance, job insecurity negative and significant influence to employee performance, and compensation satisfaction positive and significant influence to employee performance.